Financial Literacy, Financial Attitudes, and Self-Control Towards Financial Management Practice in MSME In West Nusa Tenggara - Zahari, Yudhi Kurniawan; Reza Arviciena Sakti; Abdul Basit; Oliver William Knight (Program Studi Magister Ekonomi Syariah, Fakultas Ekonomi dan Bisnis Islam, Universitas Islam Negeri Sunan Kalijaga, 2025)
This study aims to analyze the influence of financial literacy, financial attitude, and self-control on financial management behaviour among Micro, Small and Medium Enterprises (MSMEs) in West Nusa Tenggara Province. The background of this study stems from the persistent challenges of weak financial management among MSMEs, often caused by low financial literacy and poor financial attitudes. The research employs a quantitative method with a survey approach, using structured questionnaires to collect data from MSME actors across various districts and cities in the region. To test the proposed hypotheses, the data were analysed using multiple linear regression analysis, which allowed for the examination of the simultaneous influence of the independent variables on financial management behaviour. The results indicate that financial literacy, financial attitude, and self-control each have a positive and statistically significant effect on financial management behaviour. Specifically, financial literacy enhances the ability of MSME actors to budget, maintain accurate records, and plan effectively, while a positive financial attitude and strong self-control facilitate better financial decision-making. These findings underscore the importance of enhancing financial education and promoting behavioural competencies to improve financial practices among MSMEs. The study offers valuable implications for policymakers, financial institutions, and MSME stakeholders in designing empowerment strategies that incorporate both financial knowledge and behavioural reinforcement.